Étude archéozoologique du quartier portuaire romain de Saint-Lupien à Rezé/Ratiatum (Loire-Atlantique) : les vestiges fauniques en pied de berge - Aurélia Borvon (Gallia)
The faunal remains discovered during archaeological excavations carried out at the lebel of the port facilities of the Saint-Lupien quarter at Rezé/Ratiatum (Loire-Atlantique) are abundant. Preserved in a wet environment, they mainly stem from levels dated from the 1st and the 2nd c. AD. They originate from different sectors of an area called “area 4”, which refers to the different occupations of the riverbank harbour and its immediate environment over a distance of nearly 200 m. In the different parts of “area 4”, various taxa have been identified, both large-sized ones such as cattle, and very small-sized ones such as fish or shrimp. The excavation method has a very strong influence on the representation of the latter, since without fine sieving of the sediments (1.1 mm mesh size), they would be almost undetectable. Furthermore, it should be noted that while fish bones are regularly found in archaeological sites, the same is not true of the remains of shrimp carapaces. Their presence here is exceptional: they are very fragile and their preservation in this place is in part linked to the excellent preservation of the remains in a wet environment. In the western part cattle bones collected in sectors 14 and 16 are evidence of two distinct but closely related activities. Residues of craft practices are indicated by the presence of metapods showing saw marks. But most of the faunal remains appear to be food waste. There is no argument in favour of a proper butchering area (slaughtering, first stage of carcass cutting), nor of an area of domestic waste made up of food remains. The hypothesis of the presence of waste, most likely stemming from meat preparation, and of a processing workshop can be proposed to explain the characteristics of the sample studied (high proportion of cattle, representation of certain parts of the skeleton, massive use of cleaver). These characteristics thus suggest the presence of waste resulting from cutting up and deboning fleshy quarters and retrieving the marrow. The meat and marrow thus taken, probably after cooking, could be used in the manufacture of cold cuts made from bovine meat. The residues resulting from this activity were then disposed of in the Loire. Apparently these practices emerged a short time prior to the construction of the monumental quays in the second half of the 1st c. AD, i.e. when the first developments of the riverbank –of which very little is known since they are only indicated by the points of piles in the sand– were levelled and covered by the construction of large quays. Although these practices seem to be linked above all to the early settlement in the neighbourhood, the samples analysed in the case of fish, however, indicate activities that appear to be more sustainable. Indeed, the investigations carried out at either end of the harbour quarter at a distance of almost 200 m from each other from sector 16 (downstream) to sector 18 (upstream), but also in distinct places located between them, show that these ichthyological remains appear within a sequence covering the Early Roman Imperial period, i.e. between the mid-1st c. AD and the beginning of the 3rd c. AD. This makes it possible to suggest, based on the waste it left, an activity carried out in this area which was not ephemeral or transient, but long-term. These fish remains, including the presence of necessarily imported marine species, are proof of human activities. These are probably made in the form of garum-type fish sauce as indicated by the species identified and by the small estimated sizes of the individuals. The association with shrimp remains in some samples attests to the possible incorporation of these animals into this type of food preparation. The differences between the sectors, in particular as regards the skeletal representation, may be explained by differential formations of the deposits, linked to natural conditions of the context, in an open space (“natural beach” in sector 16) from which resulted a distinct scattering of the remains, or in a closed space (closed structure of sector 18) which was sealed quite rapidly. In sectors 14 and 18, the list of fish species, combined with information related to their usual biotopes, makes it possible to specify that the potential areas exploited were probably located on the foreshore, preferably sandy-muddy areas, possibly in association with areas with seagrass beds, such as those encountered nowadays in the bay of Bourgneuf. The information provided by the biotopes frequented by shrimps slightly differs in that it indicates that the possible fishing grounds were located rather towards the inner estuary. Both of these conditions were possibly present in the outer estuary, bearing in mind, however, that the use of the Loire at that time was absolutely not the same as it is today. In any case, it is not possible to completely rule out the hypothesis of separate fishing grounds (which would be the case at present). For all these small animals fishing could be done by foot, using mobile or stationary accessories, including fish locks, which operate with the tide. The lengths of the fish and the shrimp found in sector 18 makes it possible to suggest a fishing season corresponding to spring. All these remains of both fish and shrimp, could correspond to filtration residues, so as to explain their presence, with varying degrees of dispersal depending on the sector, in the harbour environment of Rezé/Ratiatum.